Management of post enucleation socket syndrome patients - A retrospective study. Issue 2 (February 2022) - Calluaud, Gauthier; Amelot, Aymeric; Kulker, Dimitri; Laure, Boris; Pare, Arnaud
Abstract: The aim of this retrospective monocentric study was to report the outcomes following the correction of post enucleation socket syndrome (PESS) as well as the factors predicting for a multistep management. Patients were included, if they had received surgery to manage PESS. Demographics and patient history were collected. The symptoms of PESS were clinically rated by the same surgeon and ocularist, preoperatively and after each procedure. The surgery was considered as successful when no PESS clinical symptoms were observed. A prognostic study was performed to investigate the surgical outcomes. Results: Thirty-six patients were included and eight of them had their PESS corrected after the first surgery. In the multivariate analysis (MVA), the deep upper lid sulcus symptom remained the main significant factor associated with an incomplete correction after the first surgery (OR 45.5, IC 95% (3.481–594.6), p = 0.004). For further corrections, the ptosis was the only significant prognostic factor requiring several surgeries (p = 0.005). At the end of the management, 94.4% of the patients had satisfying outcomes. Conclusions: The management of a PESS involves the correction of both the orbital cavity and the soft tissues. Although its correction is complex and time consuming in the majority of cases, the patients should be informed that the final cosmetic outcomes remain good at the expense of several surgeries.